Facile Synthesis of FeOOH−Ni3S2 Nanosheet Arrays on Nickel Foam via Chemical Immersion toward Electrocatalytic Water Splitting. Issue 7 (17th February 2022) - Yang, Yaqian; Mao, Han; Sun, Kuishan; Ning, Rui; Zheng, Xiaohang; Sui, Jiehe; Cai, Wei
Abstract: Electrocatalytic water splitting is a useful and promising strategy to produce hydrogen, which is a sustainable and pollution‐free supply in the future. Herein, we design the FeOOH as an improved part to enhance the excellent water splitting catalytic activities of the Ni3 S2, and the FeOOH−Ni3 S2 shows remarkable electrocatalytic performance for OER and HER compared to the pristine Ni3 S2 sample. Currently, we use a quick chemical immersion method to synthesize FeOOH on the surface of Ni3 S2 nanosheets to form a FeOOH−Ni3 S2 heterostructure. The FeOOH was formed as the dissolution process of Ni3 S2 in Fe(NO3 )3 solution. Our work opens up a quick, facile, and effective way to synthesize FeOOH and design high‐performance heterostructure electrocatalysts for energy conversion. Abstract : We design the FeOOH as an improved part to enhance excellent water splitting catalytic activities of the Ni3 S2, and the FeOOH−Ni3 S2 show remarkable electrocatalytic performance for OER and HER compared to the pristine Ni3 S2 sample. At the moment, we use a quick chemical immersion way to synthesize FeOOH on the surface of Ni3 S2 nanosheets to form FeOOH−Ni3 S2 heterostructure. The FeOOH was formed as the dissolution process of Ni3 S2 in Fe(NO3 )3 solution.